Periprocedural complication rate of carotid endarterectomy versus carotid angioplasty and stenting: a retrospective study and review of the literature - Gadoth, Avi; Auriel, Eitan; Shaim, Hila; Bornstein, Natan M. (Israel Medical Association journal, 2011)
Background: In the past, carotid endarterectomy (CEA) was the only modality for invasive intervention in cases of carotid stenosis. Due to improvements in endovascular techniques (stenting), there is a growing debate regarding the preferred procedure for carotid intervention. Objectives: To compare the 30 day complication rate after CEA and carotid angioplasty and stenting (CAS) in a tertiary medical center in Israel between the years 2008 and 2010. Methods: We reviewed the medical charts of all the patients who underwent either CEA or CAS of the internal carotid artery due to symptomatic and asymptomatic stenosis during the period 2008–2010 (total of 128 patients). Results: There was no difference between the groups in the rate of severe complications in the peri-procedural period. Mild complications were non-significantly more common in the CEA group (17%) compared to the CAS group (7.1%). Conclusions: There was no significant difference in the mild and severe complications rate between CEA and CAS in the peri-procedural period.
Gesehen am 06.07.2023